Heroes of 1776 : the story of the Declaration of Independence - Gorsuch, Neil M. (Neil McGill), 1967-; Nitze, Janie (Harper, an imprint of HarperCollins Publishers, 2026)
"The Declaration of Independence is one of the most important and beloved documents in America's history--but how did it come to be? What spurred the brave men and women to forge their own country? What sacrifices did they have to make? Why is John Hancock's signature so big? And why is Mary K. Goddard's name printed on the document too? Supreme Court Justice Neil Gorsuch and Janie Nitze walk young readers through one of America's most tumultuous times in their ... book about the foundations and ideals that make our country great. From Supreme Court Justice Neil Gorsuch and bestselling author Janie Nitze! Explore the courage and sacrifice of some of the heroes of the American Revolution and the stories behind the document that started it all--The Declaration of Independence." --